The impact of innate immunity and epigenetics in the pathogenesis of hidradenitis suppurativa - Burke, Olivia M.; Frerichs, Victoria R.; Garcia, Dario F.; Stone, Rivka C.; Lev-Tov, Hadar; Czarnowicki, Tali; Keane, Robert W.; Ojeh, Nkemcho; Marjanovic, Jelena; Pastar, Irena; Tomic-Canic, Marjana; de Rivero Vaccari, Juan Pablo; et al. (Frontiers in Immunology, 2025)
Hidradenitis Suppurativa (HS) is a chronic multifactorial inflammatory skin disease with a debilitating impact on quality of life. Here, we review the complex interplay of innate and adaptive immune dysregulation in HS pathogenesis, in the context of microbial dysbiosis, genetic predisposition, cellular dysfunction and epigenetic factors. Hyperactivation of the innate system triggered by follicular occlusion leads to a cascade of activated signaling pathways leading to persistent inflammation as the disease progresses. This immune hyperactivation is further complicated by microbiome dysbiosis, which is associated with dysregulation of inflammasomes and altered expression of host antimicrobial peptides. Keratinocytes, fibroblasts, macrophages, and neutrophils exhibit altered functions, and contribute to the inflammatory cascade and disease chronicity in HS. Epigenetic mechanisms including DNA methylation, histone modifications, and non-coding RNAs modulate immune responses and contribute to aberrant cytokine and chemokine expression that drive the persistent inflammatory state in HS pathogenesis. We highlight the need for future research to explore the concept of epigenetic memory in epidermal stem cells and inflammasome activation to gain a better understanding of these mechanisms and pave the way for development of future novel therapeutic targets and strategies to disrupt the persistent chronic inflammation cycle in this debilitating condition.